উচ্চমানৰ অসমীয়া ভাষা বোধিকা - Priyadas Talukdar; Jaysankar Das Talukdar (Sribhumi Publishing Company, Kolkata, 1991)
This is a book on Assamese language and linguistics. It traces the growth and evolution of the structural formation of the language.
Ucchamaanar Asamiya Bhaxa Bodhika
Keywords: Assamese; Grammar; Assamese